Controllable Melting and Flow of Ag in Self-Formed Amorphous Carbonaceous Shell for Nanointerconnection - Zhiqiang Yu; Qing Shi; Huaping Wang; Junyi Shang; Qiang Huang; Toshio Fukuda (Micromachines, 2022)
Nanointerconnection has been selected as a promising method in the post-Moore era to realize device miniaturization and integration. Even with many advances, the existing nanojoining methods still need further developments to meet the three-dimensional nanostructure construction requirements of the next-generation devices. Here, we proposed an efficient silver (Ag)-filled nanotube fabrication method and realized the controllable melting and ultrafine flow of the encapsulated silver at a subfemtogram (0.83 fg/s) level, which presents broad application prospects in the interconnection of materials in the nanometer or even subnanometer. We coated Ag nanowire with polyvinylpyrrolidone (PVP) to obtain core–shell nanostructures instead of the conventional well-established nanotube filling or direct synthesis technique, thus overcoming obstacles such as low filling rate, discontinuous metalcore, and limited filling length. Electromigration and thermal gradient force were figured out as the dominant forces for the controllable flow of molten silver. The conductive amorphous carbonaceous shell formed by pyrolyzing the insulative PVP layer was also verified by energy dispersive spectroscopy (EDS), which enabled the continued outflow of the internal Ag. Finally, a reconfigurable nanointerconnection experiment was implemented, which opens the way for interconnection error correction in the fabrication of nanoelectronic devices.